COP28 and the global stocktake: a weak attempt to address climate change - Aidam, Kizito (Frontiers in Sustainability, 2024)
The seminal outcome of COP28 was the Global Stocktake (GST), which referenced transitioning for the first time among all the United Nations' climate agreements. While the stocktake's GST's attempt at energy transition is welcomed, my viewpointit is that it is deficient.In this perspective this paper, the historical challenges of international climate policymaking and implementation have been explored. I argued that the stocktake is not the much-needed climate action. The challenges that undermined previous UN agreements will likely hinder COP28.Moreover, the GST's failure to use more forceful language could be a fatal flaw. Furthermore, the GST did not sufficiently define key terms like net zero and energy transition. Likewise, it did not give due consideration to energy justice. The GST missed the opportunity to take strategic advantage of state actors while creating an ecosystem for non-state actors to contribute to the fight against climate change. The GST should have taken advantage of the avalanche of scientific knowledge available on energy transition to mandate timely climate mitigation plans. Subsequent GSTs must proactively address the shortcomings of the first GST if the current generation, which is touted as the generation with the last chance to combat climate change, hopes to achieve the primary goal of the Paris Agreement.Also, the language of the stocktake is weak. The stocktake call for tripling renewable energy capacity and doubling energy efficiency has more to do with greenwashing than proactive climate action.